2007
DOI: 10.1007/s10029-007-0268-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for persistent chronic neuralgia after inguinal hernioplasty

Abstract: Following an inguinal hernia repair with open or laparoscopic technique, 1-15% of patients show persistent neuralgia, a severe, potentially debilitating, complication. Several therapeutic procedures have been proposed, but consensus regarding choice of treatment has not yet been achieved. We performed a prospective study on 32 such cases. Patients underwent anaesthetic infiltration to identify, when possible, the involved nerve, and we then carried out a step-by-step therapeutic protocol. In the initial phase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
1
18
0
1
Order By: Relevance
“…A recent scoping review on perineural steroids for the treatment of chronic post-herniorrhaphy groin pain 23 identified four case series that reported analgesic efficacy of perineural steroids around II, IH, and GF nerves in patients with CPSP following inguinal herniorrhaphy. [18][19][20][21] All of the studies reported an analgesic benefit with this intervention with a reduction in pain NRS scores by 55%-75%. However, there was heterogeneity in doses of steroids, number of injections (varying from one to seven), and interval between intervention and follow-up (one to 68 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent scoping review on perineural steroids for the treatment of chronic post-herniorrhaphy groin pain 23 identified four case series that reported analgesic efficacy of perineural steroids around II, IH, and GF nerves in patients with CPSP following inguinal herniorrhaphy. [18][19][20][21] All of the studies reported an analgesic benefit with this intervention with a reduction in pain NRS scores by 55%-75%. However, there was heterogeneity in doses of steroids, number of injections (varying from one to seven), and interval between intervention and follow-up (one to 68 months).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 There is some evidence for analgesic efficacy of injections of perineural steroids around IH and II nerves, but the published studies are heterogeneous with methodological limitations. [18][19][20][21] Existing literature is unable to provide a reliable estimate of analgesic outcomes of these procedures. There is a paucity of reliable data about the nature of pain syndromes and characteristics of patients who undergo these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…A stepwise approach to treatment, starting with the least invasive options, is recommended. 143 Although we know that the predominant mechanism for chronic postoperative pain is neuropathy following the sensitization of nerve endings of the ilioinguinal and iliohypogastric nerves, it is essential to establish the probable physiological background, e.g., hyperalgesia following nerve instrumentation, and to treat symptoms accordingly via pharmacological agents, physiotherapy, stimulation techniques, or cognitive therapy. Adjuvant pharmacological therapy may be initiated in the primary setting.…”
Section: Strategy For Treatment Of Postoperative Pain and Perspectivesmentioning
confidence: 99%
“…Other non-controlled nerve block studies in PIPP-patients have also shown analgesic responses with LA and have been used for identifying patients for neurectomy, 19 neurolysis 20 or as a treatment on its own. 21 However, significant interpretation is impeded by the lack of controls as the observed effects could be because of placebo and/or dry needling effects.…”
Section: Nerve Blockadementioning
confidence: 99%